Cuantificación de calcio en músculo de Trachurus murphyi “jurel”, Scomber japonicus “caballa”, Sarda orientalis “bonito” y Mustelus mento “tollo” que se comercializan en el mercado Mayorista, Trujillo. marzo – abril 2016 - García Cuadra, Yuliza Janeth (2016)
This research aimed to determine the concentration of calcium in four varieties of fish which were collected Wholesale Market in the city of Trujillo and muscle of the following species Trachurus murphy "Mackerel" Scomber japonicus "Mackerel" was used, striped bonito "Bonito" and speckled smooth-hound "Tollo" this was done by complexometric method. 29.97 mg of% of% 28.2mg, 23.54mg% and 21 mg% for mackerel, bonito, mackerel and found Tollo respectively